The use of metabolomics to reveal differences in functional substances of milk whey of dairy buffaloes raised at different altitudes. Issue 12 (17th May 2021) - Pu, Jinhui; Vinitchaikul, Paramintra; Gu, Zhaobing; Mao, Huaming; Zhang, Fulan
Abstract : Buffalo milk from low-altitude region contains high levels of amino acids, vitamin B6, and carbohydrates, while buffalo milk from high-altitude region contains high free fatty acid content. Abstract : Buffalo milk is nutrient-rich and contains less cholesterol than cow milk. Dairy buffaloes are widely distributed at different altitudes in the Yunnan Province, China; however, the impacts of altitude on the whey-derived functional metabolites of buffalo milk whey are not well understood. Here, we used non-targeted and targeted metabolomics to evaluate the differential metabolites in the milk whey of buffaloes raised at low altitudes (LA), medium altitudes (MA), and high altitudes (HA). ANOVA statistical test was performed to acquire differential metabolites using IBM SPSS statistics 22 software. The results showed that LA- and MA-milk whey had higher levels of amino acids (glutamine and pyroglutamic acid) and vitamin B6 than HA-milk whey. LA-milk whey had higher levels of the carbohydrates involved in galactose, amino sugar, and nucleotide sugar metabolism than MA- and HA-milk whey, but HA-milk whey showed significantly higher levels of free fatty acids. In conclusion, owing to the biological functions of their most abundant components, LA-milk is more suitable for the production of functional milk with high levels of amino acids, vitamin B6, and carbohydrates; while HA-milk is suitable as raw milk for the production of dairy products with high free fatty acid content.